Light Chain Escape in 3 Cases: Evidence of Intraclonal Heterogeneity in Multiple Myeloma from a Single Institution in Poland - Kraj, Maria; Kruk, Barbara; Endean, Kelly; Warzocha, Krzysztof; Budziszewska, Katarzyna; Dąbrowska, Monika (Case Reports in Hematology, 2015)
We report three cases of light chain escape (LCE) at a single institution in Poland, including an interesting case of biclonal monoclonal gammopathy of undetermined significance (MGUS) that satisfied the criteria for progression to light chain multiple myeloma (LCMM) with a rapid rise in serum free light chain (FLC) levels, following steroidal treatment for simultaneous temporal artery inflammation and polymyalgia rheumatica (PMR). In the three cases discussed, progression of the disease by light chain escape was associated with rapid and severe renal impairment, highlighting the necessity for prompt detection of such free light chain-only producing clones in order to prevent the possible development of irreversible end-organ damage. Interestingly, monitoring of these three patients by serum free light chain assay (sFLC) and retrospective heavy/light chain analysis (HLC) detected this clonal evolution prior to clinical relapse and suggests that these assays represent important additional tools for more accurate monitoring of multiple myeloma patients.